Identification of signal peptide features for substrate specificity in human Sec62/Sec63‐dependent ER protein import. (20th March 2020) - Schorr, Stefan; Nguyen, Duy; Haßdenteufel, Sarah; Nagaraj, Nagarjuna; Cavalié, Adolfo; Greiner, Markus; Weissgerber, Petra; Loi, Marisa; Paton, Adrienne W.; Paton, James C.; Molinari, Maurizio; Förster, Friedrich; et al.
Abstract : In mammalian cells, one‐third of all polypeptides are integrated into the membrane or translocated into the lumen of the endoplasmic reticulum (ER) via the Sec61 channel. While the Sec61 complex facilitates ER import of most precursor polypeptides, the Sec61‐associated Sec62/Sec63 complex supports ER import in a substrate‐specific manner. So far, mainly posttranslationally imported precursors and the two cotranslationally imported precursors of ERj3 and prion protein were found to depend on the Sec62/Sec63 complex in vitro . Therefore, we determined the rules for engagement of Sec62/Sec63 in ER import in intact human cells using a recently established unbiased proteomics approach. In addition to confirming ERj3, we identified 22 novel Sec62/Sec63 substrates under these in vivo ‐like conditions. As a common feature, those previously unknown substrates share signal peptides (SP) with comparatively longer but less hydrophobic hydrophobic region of SP and lower carboxy‐terminal region of SP (C‐region) polarity. Further analyses with four substrates, and ERj3 in particular, revealed the combination of a slowly gating SP and a downstream translocation‐disruptive positively charged cluster of amino acid residues as decisive for the Sec62/Sec63 requirement. In the case of ERj3, these features were found to be responsible for an additional immunoglobulin heavy‐chain binding protein (BiP) requirement and to correlate with sensitivity toward the Sec61‐channel inhibitor CAM741. Thus, the human Sec62/Sec63 complex may support Sec61‐channel opening for precursor polypeptides with slowly gating SPs by direct interaction with the cytosolic amino‐terminal peptide of Sec61α or via recruitment of BiP and its interaction with the ER‐lumenal loop 7 of Sec61α. These novel insights into the mechanism of human ER protein import contribute to our understanding of the etiology of SEC63 ‐linked polycystic liver disease. Databases: The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository (http://www.ebi.ac.uk/pride/archive/projects/Identifiers ) with the dataset identifiers: PXD008178, PXD011993, and PXD012078. Supplementary information was deposited at Mendeley Data (https://data.mendeley.com/datasets/6s5hn73jcv/2 ). Abstract : Sec61 is a membrane protein channel via which polypeptides are transported into the ER lumen or integrated into the membrane. The Sec61‐associated Sec62/Sec63 complex supports ER transport in a substate‐specific manner, but it is unclear how and which precursor polypeptides are recognised by this machinery. Here, Richard Zimmermann and co‐authors explored the mechanism of Sec62/Sec63‐driven ER import in human cells. They identified 36 precursors as Sec62/Sec63‐clients; 26 of which had signal peptides with longer but less hydrophobic H‐regions. Further analysis revealed that a slowly‐gating SP and the inhibitory effect of a positively charged cluster of amino acids are required for Sec62/Sec63 interaction.